(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify: 1- Mental flexibility among kindergarten teachers. 2- Mental flexibility among married and unmarried kindergarten teachers. 3- Mental flexibility among kindergarten teachers according to years of service.